1984
DOI: 10.1002/pol.1984.170220307
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of vinyl acetate with benzylidenemalononitrile

Abstract: Vinyl acetate was copolymerized with benzylidenemalononitrile in bulk by radical initiation at 80°C up to low conversions. Alternating copolymers were formed over a wide range of monomer feed ratios. The copolymerization parameters were determined by the conventional scheme. The copolymers were characterized by IR, proton, and 13C spectroscopy and their basic properties, solubility, viscosity, and thermal behavior were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…5). TGA thermograms of these fluoropolymers indicated that the process of degradation depends on the nature of the cyano monomer as it was observed in AN or MAN with methyl a-acetoxylacrylate copolymers [46].…”
Section: Thermal Properties Of the Copolymersmentioning
confidence: 93%
See 1 more Smart Citation
“…5). TGA thermograms of these fluoropolymers indicated that the process of degradation depends on the nature of the cyano monomer as it was observed in AN or MAN with methyl a-acetoxylacrylate copolymers [46].…”
Section: Thermal Properties Of the Copolymersmentioning
confidence: 93%
“…The incorporation of polar cyano groups in the copolymer backbone resulted in an increase of T g due to chain stiffening and marked inhibition or rotation about C-C bonds. The presence of strong CN dipoles in the backbone increases the interaction between the chains [46]. The low T g value in the poly(MVCN-co-MATRIF) copolymer arises from the low incorporation of MVCN which reduces the interaction between the main chains.…”
Section: Thermal Properties Of the Copolymersmentioning
confidence: 97%
“…(8) where [M,] (8) requires a knowledge of the concentrations of uncomplexed monomers in each of the monomer feeds. These were calculated from the initial concentrations of monomers in the feeds using the value of the equilibrium constant for the NVP-PDE monomer complex formation, K = 0.08 L/mol, which was determined by proton NMR.…”
Section: Copolymerization Studiesmentioning
confidence: 99%
“…Co-polymerization of TSE having double bonds substituted with halo, cyano and carbonyl groups, and electron-rich monosubstituted ethylenes such as styrene, N -vinylcarbazole and vinyl acetate [3][4][5] show a tendency toward the formation of alternating co-polymers. Ringunsubstituted 2-phenyl-1,1-dicyanoethylene was co-polymerized with styrene [6], vinyl acetate [7], vinyl ethers [8], methyl methacrylate [9] and N -vinyl-2-pyrrlidone [10,11].…”
Section: Introductionmentioning
confidence: 99%